Forecasting with Key Performance Indicators: Case from the Airline Industry - Kivimaa, Sanna (2025)
This master’s thesis is conducted as a case study for a relatively new subsidiary of an international airline group. The research examines forecasting and revenue management, as well as key performance indicators (KPIs) in the context of the airline industry. The thesis aims to determine what kind of KPI-based forecasting model would be most suitable for the case company. The forecasting model is developed based on previous theory and new observations made during the research process.